2021
DOI: 10.18280/acsm.450201
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Heat Transfer by Oil/Multi-Walled Carbon Nano-Tubes Nanofluid

Abstract: The subject of the study is mainly based on thermal reinforcement by an oily fluid containing nanometer particles of carbon. The study is carried out by the presence of discontinuous bars in two different shapes, i.e. flat and V, inside a horizontal heat exchanger. The study relies on simulations in thermal and dynamic terms from the literature. The turbulence effect is diagnosed by applying the k-ε model, while the flow hydrothermal transport relationships are modeled based on the finite volume technique. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Others models, such as Tiwari et al, [18], Yousef and Hassan [19], Shukla and Modi [20], and Dwivedi and Tiwari [21] have lately been used in the presence of different experimental circumstances. Moreover, there are several studies that considered the heat transfer, solar energy, energy storage, etc, in channels and enclosures, and the following are just a few examples; Hassan et al, [22], Johnson et al, [23], Alawi and Kamar [24], Abdullah et al, [25], Lubis [26], Ghalambaz et al, [27,28], Hajjar et al, [29], Menni et al, [30][31][32][33][34][35][36][37][38]40], Menni and Azzi [39], Sakhri et al, [41,42], Bendjamaa et al, [43], Boursas et al, [44], etc.…”
Section: Tablementioning
confidence: 99%
“…Others models, such as Tiwari et al, [18], Yousef and Hassan [19], Shukla and Modi [20], and Dwivedi and Tiwari [21] have lately been used in the presence of different experimental circumstances. Moreover, there are several studies that considered the heat transfer, solar energy, energy storage, etc, in channels and enclosures, and the following are just a few examples; Hassan et al, [22], Johnson et al, [23], Alawi and Kamar [24], Abdullah et al, [25], Lubis [26], Ghalambaz et al, [27,28], Hajjar et al, [29], Menni et al, [30][31][32][33][34][35][36][37][38]40], Menni and Azzi [39], Sakhri et al, [41,42], Bendjamaa et al, [43], Boursas et al, [44], etc.…”
Section: Tablementioning
confidence: 99%
“…They reported that the optimized oval-tube outperforms the conventional circular-tube shape by approximately 13% and 15% in heat transfer rates, 9% and 13.5% in coefficients of performance (COP), and 13% and 16.6% in heat transfer coefficients for Re = 1030 and 2060, respectively. Moreover, other investigations by numerical and experimental treatments have been carried out by Sakhri et al [42][43][44], Chamkha et al [45], Boursas et al [46], Chekchek et al [47], Hadidi et al [48], Menni et al [49][50][51][52], Ahmad et al [53], Salmi et al [54], Ameur et al [55], Mahammedi et al [56], Maouedj et al [57], etc. Their studies suggested different models of heat exchangers in order to improve the performance under various limit conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest improvement in the turbulence magnitude was reached in the area within a distance of two heights of the VG from the lower wall just downstream of the VG. Other related achievements are available in the literature like Sakhri et al [18][19][20], Chamkha and Menni [21], Boursas et al [22], Chekchek et al [23], Hadidi et al [24], and Menni et al [25]. Also, Salmi et al [26] tried to enhance the convective heat transfer in CHE baffles with vortex generators.…”
Section: Introductionmentioning
confidence: 99%